Patterning defects in the primary axonal scaffolds caused by the mutations of the extradenticle and homothorax genes in the embryonic Drosophila brain. - Nagao, T.; Endo, K.; Kawauchi, H.; Walldorf, U.; Furukubo-Tokunaga, K. (Development genes and evolution, 2000)
During early brain development in Drosophila a highly stereotyped pattern of axonal scaffolds evolves by precise pioneering and selective fasciculation of neural fibers in the newly formed brain neuromeres. Using an axonal marker, Fasciclin II, we show that the activities of the extradenticle (exd) and homothorax (hth) genes are essential to this axonal patterning in the embryonic brain. Both genes are expressed in the developing brain neurons, including many of the tract founder cluster cells. Consistent with their expression profiles, mutations of exd and hth strongly perturb the primary axonal scaffolds. Furthermore, we show that mutations of exd and hth result in profound patterning defects of the developing brain at the molecular level including stimulation of the orthodenticle gene and suppression of the empty spiracles and cervical homeotic genes. In addition, expression of a Drosophila Pax6 gene, eyeless, is significantly suppressed in the mutants except for the most anterior region. These results reveal that, in addition to their homeotic regulatory functions in trunk development, exd and hth have important roles in patterning the developing brain through coordinately regulating various nuclear regulatory genes, and imply molecular commonalities between the developmental mechanisms of the brain and trunk segments, which were conventionally considered to be largely independent.